Perilaku Kepemimpinan dan Motivasi terhadap Kinerja Pegawai pada Perusahaan PT. Citra Niaga Mandiri - Rahman Raising; Rahmat Hidayat; Jamaluddin, Jamaluddin (Yayasan Literasi Sains Indonesia, 2024)
The aim of this research is to determine the influence of leadership behavior and motivation on employee performance at PT Citra Niaga Mandiri Pare-Pare. This type of research uses a quantitative descriptive research method with a sample size of 70 people. The analytical methods used are linear regression analysis and correlation analysis with hypothesis testing using the T-test, F-test, and determination test (R2). The research results obtained are: (1) Leadership behavior (X1) has a positive and significant effect on the Employee Performance variable at PT Citra Niaga Mandiri (2) The Motivation variable (X2) has a positive and significant effect on the Employee Performance variable at PT Citra Niaga Mandiri (3) There is a significant simultaneous/correlated effect between leadership and motivation on employee performance at PT Citra Niaga Mandiri. Leadership behavior and motivation have a moderate effect on the employee performance of PT Citra Niaga Mandiri Parepare..